Os Pecados da Tribo, de José J. Veiga : uma leitura sob o conceito de ‘história-palimpsesto’ - Marcilio, Josué (2016)
The novel The Sins of the Tribe by the Brazilian writer José J. Veiga, is herein analyzed as a Palimpsest history. The concept is from the English critic Christine Brooke- Rose: a story created to replace the history of a people or a nation, accepted by the ruling classes, the same way a palimpsest is an erased and rewritten papyrus, where traits from the first text can be read. Gérard Genette defines the palimpsest as a form of intertextuality, or what he calls hypertextuality, a text that overlaps another, the hypotext. After presenting concepts for history and historiography we discuss aspects in which the story told in the novel has parallels with the history of Brazil during the dictatorship period. The commonalities between the novel and the specific period lived in Brazil and in Latin America, the dictatorship (the book was published in 1976) are: coups, atmosphere of insecurity, delations, submission or frustrated revolts, conspiracy. The third chapter is an attempt to demonstrate, in a structuralist approach, according to the methodology of Levi-Strauss, Barthes, and Derrida, the parallel between a chapter from the book and the myths of the deluge.